Iterative and incremental evaluation works for software development, but can it be good for student learning initiatives in Australian academic libraries? - Greenhill, Kathryn; Miller, Karen (2018)
Iterative and incremental development in software engineering involves small, ongoing “evaluate, review, act” cycles, allowing rapid development of rough prototypes of a software product that can be altered and re-tested, long before the product is considered “finished” and made available to the final stakeholders. This paper investigates whether Australian academic libraries are currently applying iterative and incremental evaluation to the development of student learning initiatives run by the library. It examines whether there are possible places in the development-cycle of these initiatives where iterative evaluation could happen, and whether it actually does happen.